Studying forests in an open schooling project - Lorena Mulero; Jordi Cunill; M. Dolors Grau; Francesc Mancho (OmniaScience, 2022)
This study involves a European Erasmus+ project with the goal to encourage Open Science Schooling (OSS), where schools help to promote community well-being in cooperation with other stakeholders. Families, enterprises and society in general are actively involved in bringing real-life projects into the classroom. It is very important the interplay of local, regional and global contexts and dynamics in shaping education and development. This study evaluates the implementation of OSS methods in each of the schools participating using questionnaires designed specifically for this project. In one of the secondary schools students study the key role forests play in the fight against climate change, and the relationship of this natural resource with several Sustainable Development Goals (SDGs).